Implementation of Complete Systematic Land Registration (PTSL) to Obtain Legal Certainty for Owners of Ready-to-Build Plots in Sungai Pelunggut Village, Sagulung District, Batam City - Butarbutar, Romasni; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1). The implementation of PTSL to obtain legal certainty for the owners of ready-to-build plots in Sungai Pelunggut Village, Sagulung District, Batam City. 2) The obstacles faced and their solutions in the implementation of PTSL to obtain legal certainty for the owners of ready-to-build plots in Sungai Pelunggut Village, Sagulung District, Batam City. This type of research falls within the scope of sociological or empirical legal research. The approach used is qualitative. The data types and sources used are primary and secondary data, obtained through interviews, observations, and literature review. The analysis is descriptive and analytical. The research results concluded: 1). The implementation of Complete Systematic Land Registration (PTSL) for Ready-to-Build Plots in Sungai Pelunggut Village reflects the state's efforts to guarantee legal certainty of land rights for the community. Normatively, this program is based on Regulation of the Minister of ATR/Head of BPN Number 6 of 2018, which serves as the main legal basis for every stage of implementation, from inventory, collection of legal and physical data, to issuance of certificates. From a legal structure perspective, the implementation of PTSL involves the Ministry of ATR/BPN, the Batam City Land Office, and local governments down to the sub-district level, which together are tasked with the administration and field verification processes. From a legal substance perspective, the clarity and uniformity of procedures in the regulations provide legal legitimacy to the land registration process. Meanwhile, from a legal culture perspective, the community is beginning to show a change in attitude towards respecting formal legality, although not yet fully widespread. 2). The implementation of PTSL for Ready-to-Build Plots in Sungai Pelunggut Village still faces various complex obstacles. Normative constraints arise from the lack of clear technical regulations regarding the legalization of plots originating from informal housing, leading to confusion in their implementation. Administrative constraints include weak documentation proving rights by applicants, especially for plots obtained through underhand agreements or without proof of legal ownership. Technical constraints include discrepancies between the physical condition of the land and legal data, as well as difficulties in determining land boundaries due to overlapping claims. Social constraints include low community participation and a lack of legal understanding regarding the importance of land certification. Solutions that have been implemented include legal counseling approaches, strengthening inter-agency coordination, utilizing mapping and measurement technology, and community empowerment. Keywords: Land Registration; Legal Certainty; PTSL.